The seventh circle : a former Australian soldier's extraordinary story of surviving seven years in Afghanistan's most notorious - Langdon , Rob (Crows Nest: Allen & Unwin, 2017)
Rob Langdon served in the Australian Army for nineteen years, before becoming a security contractor working in Iraq and Afghanistan. In June 2009 Rob was sent to assist a convoy that had been attacked by the Taliban when he shot and killed a fellow Afghan security contractor during a heated argument. Rob's claim that the guard had drawn a gun on him and that he had fired first in self-defence was dismissed by an Afghan court that refused to hear any of his evidence or call any of his witnesses, and he was sentenced to death in a matter of minutes. This was later commuted to 20 years in jail, and he served his time in Kabul's most notorious prison, Pul-e-Charkhi, described as the world's worst place to be a westerner, a sentence that was at the time acknowledged to be worse than execution. Rob was there for seven years, the longest sentence by a westerner since the fall of the Taliban, and every one of those two and half thousand days was an act of extraordinary survival in a jail run from the inside by the Taliban and filled with Afghanistan's most dangerous extremists and murderers. In 2016 Rob was pardoned and released to return to Adelaide. He's given no interviews since his release. This is his story of a seven year battle to stay alive and sane in unimaginable circumstances. Publisher